Indoxyl Sulfate Levels and Its Relation with Executive Function in Routine Hemodialysis Patients - Syafrita, Yuliarni; Susanti, Restu; Indra, Syarif; Harun, Harnavi (Global Medical & Health Communication (GMHC), 2023)
Executive function is a crucial cognitive domain that can be adversely affected by various toxic substances, including the uremic toxin indoxyl sulfate. Although it's known that indoxyl sulfate has harmful effects on intra or extra-kidney organs, its impact on executive function remains unclear. This study aimed to evaluate indoxyl sulfate levels in patients with chronic kidney disease (CKD) undergoing hemodialysis and to understand its correlation with executive function impairments. This observational cross-sectional study was conducted at the Dr. M. Djamil General Hospital Padang Hemodialysis Unit from March to July 2022; 60 patients undergoing hemodialysis and 20 healthy controls participated. Executive function was assessed using the Trail Making Test B (TMT-B). Indoxyl sulfate levels were quantified using an ELISA assay with the Assay Genie kit. The Mann-Whitney test set statistical significance at a p<0.05. The average age of the subjects was 51.4±11.4 years, with 53% being male. The mean indoxyl sulfate levels were considerably higher in the CKD group (118.79 ng/ml, range: 11–1,709 ng/ml) compared to the control group (6.028±1.829 ng/ml), with a significant difference (p<0.001). Impaired executive function was observed in 75% of the CKD patients. The average indoxyl sulfate level was 165.12 ng/ml (range: 29–1,709 ng/mL) in the impaired executive function group and 71.22 ng/ml (range: 11–333 ng/mL) in the group with normal executive function, indicating a significant difference (p=0.013). Patients with CKD undergoing hemodialysis exhibit elevated serum indoxyl sulfate levels compared to healthy individuals. Moreover, CKD patients with impaired executive function have notably higher indoxyl sulfate levels than those with normal executive function. Further research is needed to elucidate the mechanistic links between indoxyl sulfate and cognitive impairments.